Neutron activation resonance integal of 74 Ge and 76 Ge and evaluation of the keV neutron radiative capture cross section and resonance integral - Bovisio de Ricabarra, M. O.; Turjanski, Rosa; Ricabarra, Guillermo (The National Research Council of Canada, 1972)
Fil: Bovisio de Ricabarra, M. O. Comisión Nacional de Energía Atómica; Argentina